Effects of Press Needling combined with general anesthesia on postoperative analgesia in thoracoscopic pulmonary resection for lung cancer: A randomized, single-blind, controlled trial - Yueyi Jiang; Lei Wu; Yue Wang; Jing Tan; Li Wang; Jiaqin Cai; Yihu Zhou; Guowei Sun; Zhenghuan Song; Lianbing Gu (Elsevier, 2023)
Objectives: To investigate the effects of press needle therapy on postoperative analgesia and other relevant complications in patients undergoing thoracoscopic pulmonary resection. Design: randomized, single-blind, controlled trial Setting: Teaching hospitals affiliated with universities. Interventions: Eighty-six patients were randomized into: the Acu group (press-needle group) and the control group Main outcome measures: Pain levels 24, 48, and three months after surgery were measured using the numeric rating scale (NRS). Perioperative hemodynamics, total and effective pressing numbers of patient-controlled intravenous analgesia (PCIA), and incidence of postoperative pulmonary complications were recorded. Peripheral blood samples were collected to measure the levels of inflammatory mediators Results: Acu group had significantly lower NRS scores at 24 and 48 h after operation (NRS scores on movement at 24 h after surgery: Acu vs. Control, 3 (2,3) vs. 3 (3,5), Z = −3.393, P < 0.01 and NRS scores on movement at 48 h after surgery: 2 (1,3) vs. 3 (2,5), Z = −3.641, P < 0.01), lower number of PCIA attempts and effective rates (mean total pressing numbers: 4(2,8) vs. 6(3,19), Z = −1.994, P = 0.046 and mean effective pressing numbers: 3(2,8) vs. 6(3,16), Z = −2.116, P = 0.034). The Acu group had significantly reduced IL-1 (14.52 ± 3.84 vs. 16.36 ± 3.30, mean difference (MD): − 1.85, 95% confidence interval (CI): − 3.46, − 0.23, P = 0.026), HIF-1α (10.15 ± 1.71 vs. 10.96 ± 1.73, MD: −0.81, 95% CI: −1.59, −0.04, P = 0.040) and the incidence of pulmonary complications after surgery. Conclusion: Press needles are a non-invasive and feasible adjunctive intervention for postoperative analgesic management in patients undergoing thoracoscopic pulmonary resection.